The Inhibition of Prolyl Endopeptidase (PREP) by KYP-2047 Treatment to Reduce Myocardial Ischemia/Reperfusion Injury - Laura Cucinotta; Nicoletta Palermo; Alessio Ardizzone; Anna Paola Capra; Michela Campolo; Emanuela Esposito; Giovanna Casili; Marika Lanza (Antioxidants)
Myocardial ischemia–reperfusion injury (MI/R) is a negative and adverse cardiovascular outcome following myocardial ischemia, cardiac surgery, or circulatory arrest. Prolyl endopeptidase (PREP) appears to be involved in inflammatory responses, so it could be a possible therapeutic target for counteracting ischemia injury. This study aimed to investigate the role of PREP inhibitor, KYP-2047 (4-phenylbutanoyl-l-prolyl-2(S)-cyanopyrolidine), in the modulation of molecular and biochemical processes involved in MI/R. MI/R was induced through coronary artery occlusion (15 min), followed by reperfusion (2 h). KYP-2047 was intraperitoneally administrated at doses of 2.5 mg/kg and 5 mg/kg 24 h before the surgical procedures. The hearts were removed and processed for analysis. KYP-2047 treatment limited ischemic myocardial-induced histological damage and neutrophil accumulation, limiting inflammation, fibrosis, and apoptosis processes. Additionally, KYP-2047 was able to modulate p-38 and p-ERK expression, suggesting an improving role in recovering cardiac function. These findings highlighted the protective effects of KYP-2047 pretreatment in MI/R injury, suggesting PREP as a potential target therapy for the pathogenesis of MI/R. Although the molecular mechanisms underlying the action of KYP-2047 are still to be explored, these results suggested that the regulation of NF-κB, apoptosis, and MAPK pathways by KYP-2047 treatment could preventatively limit the damage caused by MI/R.